Pengaruh Gaya Hidup dan Income terhadap Financial Management Behavior - Rahmahsari, Mutmainah Dwi; Fatmawati, Elsye (Jurnal Informatika Ekonomi Bisnis, 2024)
In this era of increasingly advanced and easily accessible technology, especially information technology which offers comfort, convenience and speed in accessing various information, we are spoiled by the changes it brings, both positive and negative. This is especially seen among young people or the millennial generation, who tend to be more active in using social media. This research aims to determine the influence of lifestyle and income on financial management behavior in case studies of factory employees located in the MM2100 area, either partially or simultaneously. Sampling was carried out using random sampling technique, resulting in 95 respondents. This research collects data using a questionnaire. The data analysis techniques used include multiple linear regression analysis, hypothesis testing (t test and f test), and coefficient of determination. Data processing was carried out using the SPSS version 26 software program. The results of this research show that lifestyle and income partially or simultaneously have a significant influence on the financial management behavior of factory employees in companies located in the MM2100 area. The results of the R-Square determination test of the influence of lifestyle and income variables on financial management behavior were 94.0%. And the remaining 5.1% is influenced by other variables not included in this research.